Slow-Release Pharmaceutical Implants in Ecotoxicology: Validating Functionality across Exposure Scenarios - Bertram, Michael G; Brand, Jack A; Thoré, Eli S J; Cerveny, Daniel; McCallum, Erin S; Michelangeli, Marcus; Martin, Jake M; Fick, Jerker; Brodin, Tomas (ACS environmental Au, 2025)
Pharmaceutical contaminants have spread in natural environments across the globe, endangering biodiversity, ecosystem functioning, and public health. Research on the environmental impacts of pharmaceuticals is growing rapidly, although a majority of studies are still conducted under controlled laboratory conditions. As such, there is an urgent need to understand the impacts of pharmaceutical exposures on wildlife in complex, real-world scenarios. Here, we validate the performance of slow-release pharmaceutical implants-a recently developed tool in field-based ecotoxicology that allows for the controlled chemical dosing of free-roaming aquatic species-in terms of the accumulation and distribution of pharmaceuticals of interest in tissues. Across two years, we directly exposed 256 Atlantic salmon (Salmo salar) smolts to one of four pharmaceutical treatments: clobazam (50 μg g-1 of implant), tramadol (50 μg g-1), clobazam and tramadol (50 μg g-1 of each), and control (0 μg g-1). Fish dosed with slow-release implants containing clobazam or tramadol, or their mixture, accumulated these pharmaceuticals in all of the sampled tissues: brain, liver, and muscle. Concentrations of both pharmaceuticals peaked in all tissues at 1 day post-implantation, before reaching relatively stable, slowly declining concentrations for the remainder of the 30-day sampling period. Generally, the highest concentrations of clobazam and tramadol were detected in the liver, followed by the brain and then muscle, with observed concentrations of each pharmaceutical being higher in the single-exposure treatments relative to the mixture exposure. Taken together, our findings underscore the utility of slow-release implants as a tool in field-based ecotoxicology, which is an urgent research priority given the current lack of knowledge on the real-world impacts of pharmaceuticals on wildlife.